Seroprevalence of tick-borne encephalitis virus (TBEV) among the residents of rural areas in Sinop, central Black-Sea region, Turkey - Güneş, Turabi; Poyraz, Omer; Ataş, Mehmet; Alim, Ahmet (Mikrobiyoloji bülteni, 2010)
Tick-borne encephalitis (TBE), caused by tick-borne encephalitis virus (TBEV) is one of the serious neurological infections seen especially in the Asian and North European countries. The principal vectors of TBEV are hard ticks belonging to Ixodes genus. The major vector of European TBEV subtype is I.ricinus and the major vector of Far-Eastern and Siberian subtypes is I.persulcatus. I.ricinus exists in many climatic regions of Turkey, especially in the coastal areas. The aim of this study was to investigate the TBEV seroprevalence among the residents of rural areas in Sinop (a province located at the coast of Central Black-Sea region of Turkey). A total of 273 blood samples have been collected from the subjects (age range: 11-83 years) inhabiting in 12 villages of the central district of Sinop, during the months of May and June in 2006 and 2007. The presence of TBEV IgG antibodies in serum samples were searched by a commercial indirect fluorescent antibody kit (Euroimmun, Deutschland). TBEV IgG positivity was detected in 2.9% (8/273) of the subjects at a screening titer (1/10) and 7 (2.6%) of them also yielded positive results at further dilutions (1/100). The rates of TBEV seropositivity were not found statistically significant (p > 0.05), with respect to gender (141 of the subjects were male), age (142 of the subjects were between 21-50 years old), occupation (17 foresters, 57 were shepherds, 199 were farmers/stockbreeders) and history of tick bite (169 of the subjects had been bitten by ticks). Presence of IgG antibodies against Borrelia burgdorferi, another agent which is transmitted by the same vector, were also investigated in TBEV seropositive 8 subjects by a commercial ELISA kit (Zeus Scientific, The Netherlands). Four of these subjects yielded B.burgdorferi IgG positivity, so the TBEV - B.burgdorferi coinfection rate was estimated as 1.5% (4/273). However, since the results obtained by the tests used in this study (TBEV IgG IFA and B.burgdorferi IgG ELISA) have not been confirmed by additional confirmational tests, these subjects were referred as "probable cases". In recent years the detection rates of vector-borne viral infections is in an increment trend in Turkey due to the developments in diagnostic tests and awareness for emerging infections. In conclusion since Sinop, which is placed in the northernmost point of Turkey, is located close to TBEV endemic areas, the presence of TBEV in Sinop and the Black Sea region should always be considered.